2011
DOI: 10.1007/s10212-011-0064-7
|View full text |Cite
|
Sign up to set email alerts
|

Argumentative abilities in metacognition and in metalinguistics: a study on university students

Abstract: The article presents a study on metalinguistic, cognitive and metacognitive abilities in university students. A sample of 353 students was recruited; 178 of which from scientific and 175 from humanistic Faculties, with gender balance (M = 178; F = 175) whose age range was between 20 and 25 years old. They were administered a metalinguistic ability test that assesses metalinguistic awareness at implicit and explicit levels (L and ML scores) and the Raven's Standard Progressive Matrices 38 (SPM38). In addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
1
11
0
3
Order By: Relevance
“…Previous studies also suggest the role of gender in academic performance (Pinto, Iliceto, and Melogno 2012;Abada and Tenkorang 2009;Jacob 2002;Sheppard 2009). Sheppard (2009) found that girls with dyslexia performed significantly better than boys with dyslexia on standardised school performance tests like SATs, CAT verbal and GCSE.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies also suggest the role of gender in academic performance (Pinto, Iliceto, and Melogno 2012;Abada and Tenkorang 2009;Jacob 2002;Sheppard 2009). Sheppard (2009) found that girls with dyslexia performed significantly better than boys with dyslexia on standardised school performance tests like SATs, CAT verbal and GCSE.…”
Section: Introductionmentioning
confidence: 87%
“…Metacognition is crucial in higher education as proper use of study strategies affects academic achievements in the long term (Metcalfe 2009). Pinto, Iliceto, and Melogno (2012) demonstrated that students are fairly proficient at calling upon metacognitive skills, as evidenced by their ability to explain how they arrived at the correct solution. The authors also observed clear gender and study-related differences in that male students and students in the hard sciences outperformed female students non-verbally, whereas female students and students in humanities outperformed their male peers in all metalinguistic abilities tested.…”
Section: Introductionmentioning
confidence: 99%
“…Öğrenmenin dinamik yapısında öğretmen adaylarının anlamlı öğrenmeler gerçekleştirebilmesi, eleştirel akıl yürütme becerilerini kazanmaları açısından eğitim programlarında eleştirel düşünme ve bilişsel farkındalık süreç ve becerilerine gereken önem verilmesi alan yazın taramasında (Nielsen, 2004;Yılmaz 2007;Demir, 2009;Lee, Teo ve Chai, 2010, Semerci ve Elaldı, 2011Özsoy ve Günindi, 2011;Pinto, Iliceto, Melogno, 2012;Demir, 2013) ortaya çıkmaktadır. Bu bağlamda, bu araştırmanın çalışma grubunu oluşturan eğitim fakültesi öğrencilerinin geleceğin uzman bireyleri olacakları düşünüldüğünde, eleştirel düşünme ve bilişsel farkındalık beceri düzeylerinin belirlenmesi ile var olan profilin ortaya koyulmasının önemli olduğu düşünülmektedir.…”
Section: Ona Göre Bilişsel Farkındalık;unclassified
“…Second, previous research examined children's performance in a variety of metalinguistic tasks but did not investigate whether they were able to provide explicit justifications for their responses (Hakes, ). Consequently, we have considerable evidence concerning children's implicit (intuitive) knowledge of language rules but very limited information about the development of explicit metalinguistic awareness (Melogno, Pinto, & Levi, ; Pinto, Iliceto, & Melogno, ). In a similar vein, researchers have typically analysed children's responses to the FB questions but have never taken into account their responses to the justification questions.…”
Section: Introductionmentioning
confidence: 99%